Anthropogenically driven habitat formation by a tube dwelling diatom on the Northern Patagonian Atlantic coast. (June 2017) - Fricke, A.; Kihara, T.C.; Kopprio, G.A.; Hoppenrath, M.
Graphical abstract: Highlights: Investigation of a tube dwelling diatom as a proper indicator for eutrophication in sedimentary marine habitats. First record of B. rutilans for Argentinean waters. Combined approach of field observations and advanced microscopy (LM, CLSM). High colonization capability and growth rates of B. rutilans under eutrophication. Abstract: The tube dwelling diatom Berkeleya rutilans (Trentepohl) Grunow plays a key role as early colonizer and bloom former in coastal zones. Exuding large quantities of extracellular polymeric substances (EPS), it can form dense colonies in mucilaginous macroscopic branches, containing thousands of cells. Due to their pronounced three dimensional growths of its mucilaginous structures, it supports a variety of organisms and traps grains and detritus, which makes it an important habitat former and ecosystem engineer, contributing to sediment stabilization, which is a crucial issue in sedimentary areas. In the present study we investigated the identity and structural morphology of B. rutilans, blooming in a tidal channel in Northern Patagonia (S40° 43′ W64° 56′) and experimentally tested its potential physiological responses (e.g. growth rate) to nutrient elevation. The observed morphological plasticity and measured high growth rates under nutrient exposure make B. rutilans a likely indicator for eutrophication in sedimentary marine habitats. As to our knowledge the present study provides the first record of B. rutilans for Argentinean waters, we discussed the potential reasons for its occurrence and evaluated the ecological impacts of its presence. Due to the observed high colonization capability and rapid response to environmental alterations (e.g. eutrophication, substrate changes) it seems to benefit from human activities, which will consequently favor its further expansion within the disturbed area.